The Effectiveness of De-Radicalization Program in Southeast Asia: Does It Work? The Case of Indonesia, Malaysia, and Singapore - Suratman, Yosua Praditya (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2017)
The counterterrorism approach is still harnessed to tackle the spread of radical movement and it is deemed to be a soft strategy for a long term purpose. In the several past years, the government has been conducting de-radicalization program in attempt to bring the terrorist inmates safely to social life after the prison release. This program commonly conducted in the prison while the inmates serving the jail time for terrorism-related offences. Nevertheless, debates rise due to the fail of the program result which prove some recidivists appear to execute another terror attack. An opinion of prison environment which is considered Â as a potential breeding ground for radicalization aggravates the government effort to reintegrate the prisoners into normal society. This worsened by the activities like recruiting other prisoners and supporting extremist groups from prison which still often occur in Indonesia. Taking two examples from international scope, France has announced to close its de-radicalization program, meanwhile United States under Trumpâ€™s leadership prefer to heightened the sentences related to terrorism and to ban Muslim migrants excessively. Meanwhile, Indonesia still convinces that de-radicalization program is one of the most strategic approaches in fighting terrorism, and it is deemed as a soft power with a long term oriented. Therefore, this paper will analyze the effectiveness of the program through theories, facts, and phenomenon. Thus it will yield some recommendations for Indonesian government in strengthening and reshaping its policies.